Research on Power Producer’s Bidding Behavior Based on the Best-Response Dynamic Model - Jingqi Sun; Xiaochun Zhang; Sen Guo (Journal of Applied Mathematics)
As China’s electricity market is facing many problems, the research on power producer’s bidding behavior can promote the healthy and sustainable development of China’s electricity market. As a special commodity, the “electricity” possesses complicated production process. The instable market constraint condition, nonsymmetric information, and a lot of random factors make the producer’s bidding process more complex. Best-response dynamic is one of the classic dynamic mechanisms of the evolutionary game theory, which applies well in the repeated game and strategy evolution that happen among a few bounded rational players with a quick learning capability. The best-response dynamic mechanism is employed to study the power producer’s bidding behavior in this paper, the producer’s best-response dynamic model is constructed, and how the producers would engage in bidding is analyzed in detail. Taking two generating units in South China regional electricity market as the example, the producer’s bidding behavior by following the producer’s best-response dynamic model is verified. The relationships between the evolutionarily stable strategy (ESS) of power producer’s bidding and the market demand, and ceiling and floor price as well as biding frequency are discussed in detail.